Design of a sign chart using a new EWMA statistic. Issue 6 (18th March 2020) - Aslam, Muhammad; Ali Raza, Muhammad; Azam, Muhammad; Ahmad, Liaquat; Jun, Chi-Hyuck
Abstract: In this article, a new non parametric control chart based on the modified or controlled exponentially weighted moving average (EWMA) statistic is developed to monitor the process deviation from the target value. The proposed control chart is evaluated for different values of design parameters using the average run length as a performance criterion under various sample sizes. The proposed chart is compared with the existing non parametric EWMA sign control chart. It is observed that the proposed chart is better than the existing EWMA sign control chart in terms of run length characteristics. An empirical example is provided for the practical implementation of the proposed chart.